Design and environmental sustainability assessment of small-scale off-grid energy systems for remote rural communities. (15th January 2020) - Aberilla, Jhud Mikhail; Gallego-Schmid, Alejandro; Stamford, Laurence; Azapagic, Adisa
Highlights: 21 home and community microgrid systems are designed for remote communities. Using battery storage reduces environmental impacts of diesel generators by 20–30%. PV systems have 15% higher impacts in a micro-grid than in home installations. Hybridisation of PV and wind reduces battery requirements and impacts by up to 40%. Household-scale PV and hybrid PV-wind-battery micro-grid are the best options. Abstract: Small-scale off-grid renewable energy systems are being increasingly used for rural electrification, commonly as stand-alone home systems or community micro-grids. With the variety of technologies and configurations available, it is not clear which options are sustainable for remote communities. This study investigates the life cycle environmental sustainability of both home and community installations, designed as part of this work, which utilise diesel, solar, and wind resources coupled with battery storage. A total of 21 system configurations (six home systems and 15 micro-grids) have been designed and optimised for a prototypical rural community in the Philippines, considering both stand-alone and hybrid systems. Life cycle assessment (LCA) considering 18 potential impact categories has been carried out to compare the environmental impacts associated with electricity production of each option. At the household level, hybrid solar photovoltaics (PV)-wind systems with storage have 17–40% lower impacts than the equivalent stand-alone installations per kWh generated. Batteries are a major environmental hotspot, causing up to 88% of the life cycle impacts of a home energy system. Among the community micro-grid options, the PV-wind-lead acid battery hybrid system has the lowest impacts in many categories, including climate change, ozone depletion, and acidification. Comparing equivalent architectures for single-household and community-scale installations, PV systems are environmentally more sustainable if installed individually in households, while larger turbines in community micro-grids are environmentally better for wind utilisation. The results suggest that a household-scale PV system integrated within a micro-grid with community-scale wind turbines and Li-ion batteries is environmentally the most sustainable configuration.